1994
DOI: 10.1177/073401689401900203
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory Arrest for Domestic Violence: The Courts' Response

Abstract: Few domestic violence offenders are prosecuted for their crimes, but it is not known which offenders are most likely to receive this most serious treatment. This study examines the nature of prosecution within a state that employs a mandatory arrest policy. A population of 448 cases of intimate family violence was examined using court and police records. Only 14 percent of the offenders were found to have been prosecuted and convicted. The legal characteristics of the crime and the offender most clearly distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
0
17
2
Order By: Relevance
“…Robinson (2003) found that injuries increased the likelihood that victims would retract, as did earlier research (Rauma, 1984;Martin, 1994). However other research suggests that serious injury or severity of abuse increases the likelihood that victims will see cases through (Bennett, Goodman & Dutton, 1999;Hirschel & Hutchinson, 2001).…”
Section: Existing Research On Victim Retractionmentioning
confidence: 89%
“…Robinson (2003) found that injuries increased the likelihood that victims would retract, as did earlier research (Rauma, 1984;Martin, 1994). However other research suggests that serious injury or severity of abuse increases the likelihood that victims will see cases through (Bennett, Goodman & Dutton, 1999;Hirschel & Hutchinson, 2001).…”
Section: Existing Research On Victim Retractionmentioning
confidence: 89%
“…Mandatory arrest and no-drop prosecution policies are examples of attempts to change attitudes that IPV is without consequences. Creating a community atmosphere in which consequences are swift and certain is hoped to deter violence by addressing both the likelihood and negativity of consequences (Martin, 1994). These attitudes are also related to social norms.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…As a result of the strengthening of criminal justice response to IPV in the mid-1980s, the number of individuals mandated into batterer intervention services (BIS) programs increased dramatically (Hamberger & Arnold, 1990;Martin, 1994). Concern arose among social activists that services were not developed and implemented based on prominent theories of IPV (Austin & Dankwort, 1998).…”
mentioning
confidence: 98%
“…When police discretion is constrained, might particular situational factors become more salient in shaping the helping behavior of police? Large variation across police departments, as evident in such perverse consequences as dual arrest (Martin, 1994) may suggest that organizational characteristics are critical to the satisfactory encounter between police and victim. The study of victim satisfaction should include both qualitative and quantitative methods; employ multiple dimensions of satisfaction; and use samples large enough to study the evaluation of minority victims.…”
Section: Resultsmentioning
confidence: 97%